PENGUJIAN KEMBALI TEORI PECKING ORDER PADA PERUSAHAAN NON KEUANGAN YANG BERTUMBUH DAN MAPAN DI BURWSA EFEK INDONESIA - , Dian Paula Sabatini; , Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research was to re-test the pecking order theory on growth and mature non financial company at Indonesia stock exchane. Analyzed variables are firm size, growth assets, tangibility, liquidity, and profitability. Researh using cross section and time series methode for taking samples, with criterias: (1) Non financial public company listed at LQ 45 Index Indonesia Stock Exchange by period 2009-2011 (2) avaliable data annual financial statements and balance sheet during the period of study (period 2008 to 2011) (3) (2) avaliable data cash flow statement during the period of study (period 2009 to 2011). Data obtained on the basis of the publication on Indonesia Capital Market Directory (ICMD), obtained 72 samples of growth and mature companies, Analysis technique used is multiple regression analysis. Results of research showed pecking order theory is the structure modal theory that mostly used by non financial companies in Indonesia.